Differences in workers' compensation claim rates for within‐province and out‐of‐province workers in British Columbia, Canada, 2010–2017. Issue 3 (28th January 2022) - Macpherson, Robert A.; Neis, Barbara; McLeod, Christopher B.
Abstract: Background: Little is known about the work‐related injury and illness risk of out‐of‐province workers. This study examines whether there are differences in work‐related injury and illness claim rates between within‐province and out‐of‐province workers in British Columbia (BC), Canada. Methods: Workers' compensation claim data for injuries and illnesses in BC from 2010 to 2017 were linked with denominator data from Statistics Canada. Multivariable negative binomial regression estimated the claim rate ratio (RR) and 95% confidence intervals (CI) for out‐of‐province workers with all, health care‐only (HCO), short‐term disability, long‐term disability, and fatality (SLF), and serious injury (SI) claims, compared to within‐province workers. Results: Compared to within‐province workers, out‐of‐province workers had a lower total claim rate (RR: 0.54, 95% CI: 0.52–0.57), adjusting for sex, age, industry sector, and year. Differences in rates differed by claim type, with the largest differences for HCO claims (RR: 0.49, 95% CI: 0.47–0.52) and smallest differences for SI claims (RR: 0.85, 95% CI: 0.78–0.92). Sex‐stratified models showed larger differences for males than females, with older female out‐of‐province workers having elevated SI claim rates. Industry‐specific models showed that, even in sectors with high proportions of out‐of‐province workers' claims, these workers have lower claim rates than within‐province workers. Conclusions: Out‐of‐province workers generally have lower claim rates than within‐province workers. The overall duration of work exposure, and underreporting or underclaiming, are factors that may explain these lower claim rates. Understanding the determinants and differences of these claim rates may improve the administration and adjudication of claims while also identifying where further prevention measures may be merited.